Sphalerites characterization by optical microscopy method - Quiñones, Janet (2013)
This research‘s main objective quantification of iron content in sphalerites; differentiation of three types of sphalerites is obtained according to the iron content, which will be useful for the proposed solutions in the metallurgical problems. In this study themineralogical characterization of samples from the Paragsha concentrator, the mining district of Cerro de Pasco and especiallysphalerites using the method of optical microscopy was performed for which it was necessary to use a polarizing microscopereflected light.Studies was performed as accurately as in the case of modal analysis where estimates of the degree of liberation and mineralgicalassociation are made, the samples come from the metallurgical testing laboratory. The specimen was taken from the concentratorplant Paragsha, then sifted for the preparation of polished sections that were used for the characterization of each independently.Mineralogical analysis showed us that the samples consist of sphalerite 1 sphalerite 2 3 sphalerite, galena, tennantite, hematite,pyrite, arsenopyrite, pyrrhotite, marcasite, chalcopyrite, magnetite and bargains. Detailed analysis of the zinc concentrate samplesmineralogical study reveals whether it is making the metallurgical process correctly or for improvingthe development process that is taking place in the indicate the various difficulties encountered during the stage of grinding, these release rates are givenin percentages of free particles and the type of entanglement between different minerals. The results of the mineralogical characterizationstudiesareessentialbecausetheyallowexplainspecificphenomenaoccurringduringmetallurgicalprocesses.Ionareessential because they allow mineralogical explain specific phenomena occurring during metallurgical processes.